Intelligent Materials Tracking System for Construction Projects Management - Narimah Kasim (Journal of Engineering and Technological Sciences, 2015)
An essential factor adversely affecting the performance of construction projects is the improper handling of materials during site activities. In addition, paper-based reports are mostly used to record and exchange information related to the material components within the supply chain, which is problematic and inefficient. Generally, technologies (such as wireless systems and RFID) are not being adequately used to overcome human errors and are not well integrated with project management systems to make tracking and management of materials easier and faster. Findings from a literature review and surveys showed that there is a lack of positive examples of such tools having been used effectively. Therefore, this research focused on the development of a materials tracking system that integrates RFID-based materials management with resources modelling to improve on-site materials tracking. Rapid prototyping was used to develop the system and testing of the system was carried out to examine the functionality and working appropriately. The proposed system is intended to promote the employment of RFID for automatic materials tracking with integration of resource modelling (Microsoft (R) Office Project) in the project management system in order to establish which of the tagged components are required resources for certain project tasks. In conclusion, the system provides an automatic and easy tracking method for managing materials during materials delivery and inventory management processes in construction projects.